2020
DOI: 10.3389/fpsyg.2020.560188
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic Moral Self-Completion – Social Recognition of Prosocial Behavior Reduces Subsequent Moral Striving

Abstract: According to theories on moral balancing, a prosocial act can decrease people's motivation to engage in subsequent prosocial behavior, because people feel that they have already achieved a positive moral self-perception. However, there is also empirical evidence showing that people actually need to be recognized by others in order to establish and affirm their self-perception through their prosocial actions. Without social recognition, moral balancing could possibly fail. In this paper, we investigate in two l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…Social recognition is about public acknowledgment of people's status, merits, or personality (Susewind and Walkowitz, 2020). Maslow's (1970) hierarchy of needs classifies human needs into five levels to motivate human behavior.…”
Section: Social Recognitionmentioning
confidence: 99%
“…Social recognition is about public acknowledgment of people's status, merits, or personality (Susewind and Walkowitz, 2020). Maslow's (1970) hierarchy of needs classifies human needs into five levels to motivate human behavior.…”
Section: Social Recognitionmentioning
confidence: 99%
“…Given that we could not replicate C&P's proposed moderation by conceptual abstraction, it may also be important to reconsider other hypothesized moderators in sequential moral behavior (e.g., Brown et al, 2011;Griep et al, 2021;Lalot et al, 2022;Susewind & Hoelzl, 2014;Susewind & Walkowitz, 2020). Understanding the factors that regulate whether doing good or bad leads to similar or opposite behavior afterward is crucial not only in moral psychology but also in domains such as organizational (List & Momeni, 2021) and consumer (Juhl et al, 2017) behavior.…”
Section: Discussionmentioning
confidence: 89%
“…To reconcile the debate between sequential moral consistency and compensatory behavior, several studies have examined potential moderating factors determining when each is more likely to occur. Research shows compensatory (consistency) moral behavior is more likely when people adopt a concrete (abstract) mental construal (Brown et al, 2011;Conway & Peetz, 2012), are oriented toward an outcome-based (rule-based) ethical mindset (Cornelissen et al, 2013), have a goal progress (commitment) mindset (Susewind & Hoelzl, Running head: MORAL CONSISTENCY OR COMPENSATION 2014), (do not) feel social recognition of the initial good behavior (Susewind & Walkowitz, 2020), focus on the past (future) organizational citizenship behavior (Griep et al, 2021), or have prevention (promotion) regulatory focus (Lalot et al, 2022). This stream of research suggests that the moral consistency vs. compensatory behavior debate may not be about which is more likely but when is each more likely.…”
Section: Consistency or Compensatory Behavior? A Registered Replicati...mentioning
confidence: 99%
“…Social environments can also affect moral decision-making. Susewind and Walkowitz (2020) found that social recognition of prosocial acts led to less subsequent helpful behavior compared to prosocial acts that were unrecognized (e.g. anonymously donating to charity).…”
Section: Moral Decision Makingmentioning
confidence: 94%